Dampak Budaya Organisasi terhadap Inovasi dalam Perusahaan Teknologi: Sebuah Penelitian Kualitatif - Putri, Naulya Dwi; Haslindah, Haslindah; Marwati, Putri Kharisma Shafah; Hermawansyah, Wira; Bustan, Bustan; Ilahi, Andi Alfianto Anugrah (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
Innovation is crucial to technology companies' success in an ever-changing environment. Organizational culture has been identified as a factor capable of influencing a company's innovation level. This qualitative research explores this further by examining how organizational culture affects innovation in technology companies. Our literature review covers the concepts of corporate culture innovation and relevant previous research. We used a qualitative approach involving in-depth interviews with leaders and members of innovation teams at several leading technology companies. This research reveals a complex relationship between elements of organizational culture, such as norms, values, organizational structure, and innovation. This research provides a deeper understanding of the cultural factors that can motivate or hinder the innovation process in technology companies. The practical implications of this research include suggestions for companies to design an organizational culture that supports sustainable innovation. The results of this research provide important insights for technology companies seeking to increase their level of innovation in an ever-evolving world. By understanding the impact of organizational culture on innovation, companies can design more effective strategies to remain competitive in an era of ever-changing technology.